TINJAUAN TEORITIK MODEL-MODEL KEKUASAAN - Pawito, Pawito; Tiyanto, Dwi; Utari, Prahastiwi (Jurnal Masyarakat dan Budaya, 2003)
This essay deals with power, especially in terms of politics.After a short discussion of the definitions of power, this essay emphasizes models of power with illustrations of the implementation of power in the Indonesian context. The models of power include the voluntary, hermeneutic, structural, and post-modernism model of power.